Respuesta :
we are given
parent function as
[tex]y=x^2[/tex]
(1)
vertical stretch of factor 2
so, we can multiply y-value by 2
[tex]y=2x^2[/tex]
then a shift right of 3 units
so, we can replace x as x-3
[tex]y=2(x-3)^2[/tex]
(2)
a shift left by 2 units
we can replace x as x+2
[tex]y=(x+2)^2[/tex]
then a horizontal shrink factor of 1/2
so, we can multiply by 2 to x-value
[tex]y=(2x+2)^2[/tex]
then a shift down of 5 units
we can subtract y-value by 5
so, we get
[tex]y=(2x+2)^2-5[/tex]
(3)
a shift to the right 1 unit
we can replace x as x-1
[tex]y=(x-1)^2[/tex]
stretched vertically by a factor of 1/2
we can multiply y-value by 1/2
[tex]y=\frac{1}{2} (x-1)^2[/tex]
then is shifted down 4 units
we can subtract y-value by 4
[tex]y=\frac{1}{2} (x-1)^2-4[/tex]
(4)
reflected across the x-axis
we can multiply y-value by -1
[tex]y=-x^2[/tex]
tretched vertically by a factor of 3
multiply y-value by 3
[tex]y=-3x^2[/tex]
shifted left 7 units
we can replace x as x+7
[tex]y=-3(x+7)^2[/tex]